THE USE OF MODERN EDUCATIONAL TECHNOLOGIES IN TEACHING THE TOPIC OF ”SALTS" - Karimova Dilovar Batirovna; Jo’raqo’ziyeva Nilufar Bahodirjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Innovative educational technologies for studying the topic of "salt" in chemistry teaching suggest that when using interactive methods, students’ activity increases and interest in learning activities increases, communication skills and a positive attitude to the topic under consideration are formed.